The impact of mobile-assisted swimming applications on intrinsic motivation and fear reduction in aquatic environments among students in the swimming course - Alkasasbeh, Walaa Jumah; Alawamleh, Thekra; Aloran, Hasan; Farash, Tamara; Orhan, Bekir Erhan (Frontiers in Sports and Active Living, 2024)
The study explored the impact of mobile-assisted swimming applications on intrinsic motivation and fear reduction in aquatic environments among students in the Swimming Course. The study sample consisted of 69 male and female students enrolled in the "Swimming Education and Training" course. The Intrinsic Motivation Scale and the Water Fear Assessment Questionnaire were used to collect data. The results showed no statistically significant differences in motivation levels before and after using the application. However, the results did show a statistically significant reduction in fear of water after using the application. Furthermore, no statistically significant relationships were found based on demographic variables (gender, academic year, parental swimming practice, or university GPA) for either motivation or fear reduction. These findings reinforce the potential value of assistive applications in reducing students' fear of water and supporting swimming skill acquisition, while highlighting the role of technology in enhancing students' learning experience .